Penanaman nilai-nilai Nasionalisme melalui pembelajaran kewarganegaraan di sekolah - Hapsari, Laura Yesica julya (Maliki Interdisciplinary Journal, 2025)
Nationalism education plays a crucial role in shaping the character and national identity of Indonesia’s youth. The instillation of nationalist values through Citizenship Education in schools is expected to enhance patriotism and strengthen national unity. This study aims to examine the importance of instilling nationalist values through Citizenship Education, focusing on the learning materials, teaching methods, and the school culture that supports the strengthening of national identity. The research method used includes a literature review and observation of teaching practices in schools. The findings indicate that Citizenship Education, along with routine school activities such as flag ceremonies, community service, and morning exercises, is highly effective in instilling nationalist values in students. Furthermore, a relevant curriculum and creative teaching methods are necessary to ensure that these national values are well understood and applied by students. It is recommended that nationalism education be continually updated to align with the times, involving the role of families and communities in supporting the process. With the strengthening of nationalism education, it is hoped that the younger generation will grow into responsible, principled individuals with a strong sense of nationalism.